Activity of Muntingia calabura Leaves Ethanolic Extract on Glucose and Insulin Blood Levels in Streptozotocin-induced Rat - Syahara, Suci; Harahap, Urip; Widyawati, Tri (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The research aims to determine the effect of Muntingia calabura leaves extract on improving diabetes conditions, by analyzing blood glucose and insulin levels of male Rattus novergicus which is given high fat diet and induce streptozotocin 30 mg/kg BB with a two-week interval. Design: This research was a purely experimental with pretest and post test control group design. This research was divides into 6 groups. Three treatment groups were treated by Muntingia calabura leaves extract with the doses of 125, 250, and 500 mg/kg. Other groups are negative control (CMC-Na), positive control (glibenklamid) and normal control. Interventions: The variables specified in this study are variations in the concentration of extract used. variations in extract concentration are expected to affect the results of glucose concentration and blood insulin in rats. Main outcome measure: The main parameters measured in this study were rat blood glucose and insulin levels. Results: The result of this research indicate that the ethanol extract of Muntingia calabura leaves able to reduce blood glucose levels effectively at dose 500 mg/kg (97, 17 mg/dL) so that insulin levels increase well (0,839 µg/mL). Conclusion: Muntingia calabura leaves ethanol extract can reduce glucose levels and increase blood insulin levels in rats.